Bài tập  /  Bài đang cần trả lời

Giải phương trình

----- Nội dung dịch tự động từ ảnh -----
e)
3
3x+1
2
x-5
+
1-3x
9x²-1
2 Xem trả lời
Hỏi chi tiết
67
Tham khảo câu trả lời từ Trợ lý ảo Lazi
To solve the equation

\[ \frac{3}{3x+1} + \frac{2}{1-3x} = \frac{x-5}{9x^2-1}, \]

we start by simplifying the right-hand side of the equation.

Notice that \( 9x^2 - 1 \) can be factored as a difference of squares:

\[ 9x^2 - 1 = (3x + 1)(3x - 1). \]

So the equation becomes:

\[ \frac{3}{3x+1} + \frac{2}{1-3x} = \frac{x-5}{(3x+1)(3x-1)}. \]

Next, we need to find a common denominator for the fractions on the left-hand side. Notice that:

\[ 1 - 3x = -(3x - 1). \]

So we rewrite the second fraction:

\[ \frac{2}{1-3x} = \frac{2}{-(3x-1)} = -\frac{2}{3x-1}. \]

Now the equation is:

\[ \frac{3}{3x+1} - \frac{2}{3x-1} = \frac{x-5}{(3x+1)(3x-1)}. \]

The common denominator for the left-hand side is \((3x+1)(3x-1)\). Rewrite the fractions with this common denominator:

\[ \frac{3(3x-1)}{(3x+1)(3x-1)} - \frac{2(3x+1)}{(3x+1)(3x-1)} = \frac{x-5}{(3x+1)(3x-1)}. \]

Simplify the numerators:

\[ \frac{3(3x-1) - 2(3x+1)}{(3x+1)(3x-1)} = \frac{x-5}{(3x+1)(3x-1)}. \]

Expand and combine like terms in the numerator:

\[ \frac{9x - 3 - 6x - 2}{(3x+1)(3x-1)} = \frac{x-5}{(3x+1)(3x-1)}. \]

\[ \frac{3x - 5}{(3x+1)(3x-1)} = \frac{x-5}{(3x+1)(3x-1)}. \]

Since the denominators are the same, we can equate the numerators:

\[ 3x - 5 = x - 5. \]

Subtract \(x\) from both sides:

\[ 2x - 5 = -5. \]

Add 5 to both sides:

\[ 2x = 0. \]

Divide by 2:

\[ x = 0. \]

So the solution to the equation is:

\[ x = 0. \]

We should check if \( x = 0 \) is valid by substituting it back into the original equation to ensure it does not make any denominator zero. Substituting \( x = 0 \):

\[ \frac{3}{3(0)+1} + \frac{2}{1-3(0)} = \frac{0-5}{9(0)^2-1}, \]

\[ \frac{3}{1} + \frac{2}{1} = \frac{-5}{-1}, \]

\[ 3 + 2 = 5, \]

\[ 5 = 5. \]

So \( x = 0 \) is indeed a valid solution.
2
0
Trúc Mai
21/07/2024 14:06:46
+5đ tặng
đề
=> 3/(3x + 1) - 2/(3x - 1) = (x - 5) / (3x + 1)(3x - 1)
=> 3.(3x - 1) - 2.(3x + 1) = x - 5
=> 9x - 3 - 6x - 2 = x - 5
=> 3x - x = -5 + 3 + 2
=> 2x = 0
=> x = 0

Mở khóa để xem toàn bộ nội dung trả lời

(?)
Bạn đã đạt đến giới hạn của mình. Bằng cách Đăng ký tài khoản, bạn có thể xem toàn bộ nội dung trả lời
Cải thiện điểm số của bạn bằng cách đăng ký tài khoản Lazi.
Xem toàn bộ các câu trả lời, chat trực tiếp 1:1 với đội ngũ Gia sư Lazi bằng cách Đăng nhập tài khoản ngay bây giờ
Tôi đã có tài khoản? Đăng nhập
1
0
Trung Trần
21/07/2024 14:09:36
+4đ tặng
đề bài (đkxđ x#±1/3 x)
<=> 3/(3x + 1) - 2/(3x - 1) = (x - 5) / (3x + 1)(3x - 1)
=> 9x - 3 - 6x - 2 = x - 5
<=> 3x - x = -5 + 3 + 2
<=> 2x = 0
<=> x = 0
vậ pt có ngh x=0

Bạn hỏi - Lazi trả lời

Bạn muốn biết điều gì?

GỬI CÂU HỎI
Học tập không giới hạn cùng học sinh cả nước và AI, sôi động, tích cực, trải nghiệm

Hôm nay bạn thế nào? Hãy nhấp vào một lựa chọn, nếu may mắn bạn sẽ được tặng 50.000 xu từ Lazi

Vui Buồn Bình thường
×
Trợ lý ảo Trợ lý ảo
Gửi câu hỏi
×